SUFISM THOUGHTS MURTAZA MOTAHHARI The Relations and Unity Between Intellectuality (Science), Spirituality (Faith) and Morality (Morals) - Sabara, Sabara (Journal of Islam and Science, 2016)
This paper is a review of Sufism thoughts of a contemporary Iranian thinker, namely Murtaza Motahhari. It focuses on discussing the relation and unity of science, faith, and morals in the frame of Sufism thought. Murtaza Motahhari adopted the view of philosophical sufism or irfan. It deals with the view of Sufism based on the assumptions of rational philosophy in understanding the reality of the inner (spiritual) or irfan ilmi (theoretical) and the practices of sharpening intuitive with the path of mysticism or irfan amali (practical). The process of Suluk journey started from philosophical ma'rifat (ma'rifat ilmi) continued with the practice of Shari'a, congregations, nature, until achieving the true ma'rifat. It is the irfan concept as understood in the spiritual world of Shia. People who follow the irfan is called wise. By following Suluk (mysticism) a Arif will be increasingly forged a soul consciousness to increasingly realize the moral act in practical terms. Irfan is built on the foundation of philosophy about theology and teopani as forming the spiritual consciousness actualized through amaliah and akhlakul karimah. Maqamat reached and passed is what is achieved by a Arif through his work. Meanwhile, hal is what alight heart of a Arif. There are six maqams passed in Irfan, namely maqam nafs, maqam qalb, maqam, spirit, maqam sirr, maqam khafy, and maqam akhfa.